2011
DOI: 10.7773/cm.v37i4a.1920
|View full text |Cite
|
Sign up to set email alerts
|

Wind-driven coastal circulation in the Gulf of Tehuantepec, Mexico

Abstract: Sea surface current measurements and wind stress and sea surface temperature satellite data were used to study the effect of northerly wind events (Tehuanos) on coastal dynamics in the Gulf of Tehuantepec, Mexico. The winter 2005 observations show a significant change in the intensity and direction of surface currents during wind events, which is reflected in an increase in kinetic energy and negative relative vorticity. The analysis revealed that kinetic energy of the coastal current decreases (increases) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 18 publications
1
9
1
3
Order By: Relevance
“…Another mesoscale structure of importance in relation to carbon chemistry in the GoT is the coastal current that flows to the northwest. Although this has been reported previously as a surface current by other authors [ Barton et al ., ; Flores‐Vidal et al ., ; Machain‐Castillo et al ., ; Velázquez‐Muñoz et al ., ], in the present study, it occurred as a surface current to the east and a subsurface one to the west. This current functions as a DIC advection mechanism.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Another mesoscale structure of importance in relation to carbon chemistry in the GoT is the coastal current that flows to the northwest. Although this has been reported previously as a surface current by other authors [ Barton et al ., ; Flores‐Vidal et al ., ; Machain‐Castillo et al ., ; Velázquez‐Muñoz et al ., ], in the present study, it occurred as a surface current to the east and a subsurface one to the west. This current functions as a DIC advection mechanism.…”
Section: Discussioncontrasting
confidence: 61%
“…Temporal coverage of data used in this study is not enough to discern whether this flow is a constant current or derives from eddy rims associated mainly with cyclonic eddies (Figure ). Previous studies refer to a poleward coastal current detected at the same region during winter, spring, and summer [ Barton et al ., ; Flores‐Vidal et al ., ; Trasviña and Barton , ; Willett et al ., ; Velázquez‐Muñoz et al ., ]. Furthermore, geostrophic velocity in section I (Figure ) indicates a poleward subsurface flow in spite of the coastal upwelling and the anticyclonic eddy.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Mesoscale eddies are generated in winter (dry season) (Trasviña & Barton, 2008) directly associated with the Tehuan events, jet winds locally called "Tehuanos, Tehuantepecanos or Nortes" (Trasviña et al, 2003;Reyes-Hernández et al, 2016), although it has also been observed that eddies non-associated to the wind can be produced (Flores-Vidal et al, 2011). The currents and sea surface temperature show temporal variability near the coast of the GT when these events occur in the winter (Velázquez-Muñoz et al, 2011), particularly upwelling in the GT and a notable decrease in sea surface temperature (Trasviña et al, 2003). In this area there is a coastal current of approximately 100 km wide, that flows from westwards, which can be persistent throughout the year causing the entry of a warm water mass to the GT (Velázquez-Muñoz et al, 2011).…”
Section: Meterials and Methodsmentioning
confidence: 99%
“…The currents and sea surface temperature show temporal variability near the coast of the GT when these events occur in the winter (Velázquez-Muñoz et al, 2011), particularly upwelling in the GT and a notable decrease in sea surface temperature (Trasviña et al, 2003). In this area there is a coastal current of approximately 100 km wide, that flows from westwards, which can be persistent throughout the year causing the entry of a warm water mass to the GT (Velázquez-Muñoz et al, 2011). It has also been shown that the flow of this surface current is interrupted by Tehuano winds of moderate to strong intensity (Reyes-Hernández et al, 2016).…”
Section: Meterials and Methodsmentioning
confidence: 99%